Per una narratologia postumanista. Bruce Clarke, Posthuman Metamorphosis: Narrative and Systems (ENTHYMEMA, 2010)
Review of Clarke Bruce. Posthuman Metamorphosis: Narrative and Systems. New York: Fordham University Press, New York, 2008. Print. In this study we reconstruct the story of a little-known tale by Leo Tolstoy, What Men Live By? (1881). Tolstoy’s aim with this work was to illustrate certain key aspects of the new ethical-religious vision he had developed during the 1870s. On completing What Men Live By, the author took an active part in distributing it among both the urban and rural working classes; his efforts were successful and it was effectively read by millions of working-class people. On the one hand, our article looks at the narrative and editorial strategies Tolstoy adopted to win over new readers; on the other hand, it analyzes the tactics adopted by his working-class readers to appropriate, adapt and transform Tolstoy’s text for themselves.